The Impact of Sharia Certification on Nutrition Management at YARSI Hospital - Sri Rahayu; Pradnya Paramitha; Vican Sefiany Koloi; Lanlan Lesmana; Wahyu Sulistiadi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Sharia certification guarantees the ummah's need for Islamic standardized health services, including food services for hospital patients. Nutrition management includes planning, organizing, implementing nutrition services, supervising nutrition services, and evaluating. YARSI Hospital has received sharia certification from the National Certification Council-Majelis Ulama Indonesia, hoping to benefit hospitals and users of halal, safe and tayyib nutrition services and social transformation for the community. This research aims to analyze the impact of Sharia certification on nutrition management at YARSI Hospital, which consists of planning, organizing, implementing nutrition services, supervising nutrition services, and evaluating. Descriptive analytics followed by a different "Wilcoxon Signed Ranks Test" test with a cross-sectional approach. The sample for filling out the questionnaire was 24 respondents, and for the interview was 1 respondent. Respondents are the managers of the nutrition installation of YARSI Hospital. The certification proved an increase in the assessment of being better in nutrition management before and after Sharia certification. Respondents gave an average assessment (positive ranks) after Sharia certification> (greater) than before Sharia certification, and there was a significant difference because of the Asymp. Sig. (2-tailed) on all factors was < than the value of α (0.05). YARSI Hospital's nutrition services are committed to implementing halal, safe and tayyib nutrition services and are expected to become an example for other hospitals to obtain Sharia certification.